An initial framework for use of ultrasound by speech and language therapists in the UK: Scope of practice, education and governance. (May 2023) - Allen, Jodi Elizabeth; Cleland, Joanne; Smith, Mike
Background: There is growing evidence to support the use of ultrasound as a tool for the assessment and treatment of speech, voice and swallowing disorders across the Speech and Language Therapy profession. Research has shown that development of training competencies, engagement with employers and the professional body are vital to progressing ultrasound into practice. Methods: We present a framework to support translation of ultrasound into Speech and Language Therapy. The framework comprises three elements: (1) scope of practice, (2) education and competency and (3) governance. These elements align to provide a foundation for sustainable and high-quality ultrasound application across the profession. Results: Scope of practice includes the tissues to be imaged, the clinical and sonographic differentials and subsequent clinical decision-making. Defining this provides transformational clarity to Speech and Language Therapists, other imaging professionals and those designing care pathways. Education and competency are explicitly aligned with the scope of practice and include requisite training content and mechanisms for supervision/support from an appropriately trained individual in this area. Governance elements include legal, professional and insurance considerations. Quality assurance recommendations include data protection, storage of images, testing of ultrasound devices as well as continuous professional development and access to a second opinion. Conclusion: The framework provides an adaptable model for supporting expansion of ultrasound across a range of Speech and Language Therapy specialities. By taking an integrated approach, this multifaceted solution provides the foundation for those with speech, voice and swallowing disorders to benefit from advances in imaging-informed healthcare.